If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72x + -89 = x + -81 Reorder the terms: -89 + 72x = x + -81 Reorder the terms: -89 + 72x = -81 + x Solving -89 + 72x = -81 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -89 + 72x + -1x = -81 + x + -1x Combine like terms: 72x + -1x = 71x -89 + 71x = -81 + x + -1x Combine like terms: x + -1x = 0 -89 + 71x = -81 + 0 -89 + 71x = -81 Add '89' to each side of the equation. -89 + 89 + 71x = -81 + 89 Combine like terms: -89 + 89 = 0 0 + 71x = -81 + 89 71x = -81 + 89 Combine like terms: -81 + 89 = 8 71x = 8 Divide each side by '71'. x = 0.1126760563 Simplifying x = 0.1126760563
| (2*4y)+(2*5y)=0 | | (3z+2)(4-z)=0 | | 15+10x=13x | | 10(X)=X-7 | | 4(8n-3)+7n= | | G-2/7=6 | | 4(r+1)= | | 0=-5x^2+3x^2 | | 4+4(3x-2)=-2(4x-6)+8x | | 4+4(3x-2)=-2(4x-6) | | 0=-5x^2+3x^2ln(x) | | 2x*2x-3=9 | | 21+3y-3=12y-12-4y | | -3.5w+0.1=0.2w-3.6 | | a^2=-12a | | 9+ln(20x)=17-2ln(x) | | 6y+3=4y+11 | | -6(-3w+6)-3w=6(w-2)-9 | | 2k^2+12k-70=-2 | | 2cos^2-3cosx=0 | | 2(x+3+7)=x | | 2x+6=4x-28 | | (3z-2)(4-z)=0 | | 11/13=9/u | | x((y+3)(y-3))+6=0 | | (3x+3)x=6 | | 40+x+2y=180 | | 2x+0.9=3x-3.1 | | 2(v+5)=-2(7v-4)+8v | | 4.5x+7=25 | | 8u+16=-4(-2u-4) | | 2(v+5)=-2(7v-4) |